Effects of sildenafil on the viability of random skin flaps - Barral,Sumara Marques (2011)
PURPOSE: To assess the viability of McFarlane skin flaps in rats with administration of sildenafil. METHODS: Twenty Wistar rats were distributed into two groups: Control (dorsal skin flap, subdermal application of saline solution at 0.9%) and Study (dorsal skin flap, subdermal application of sildenafil). Seven days after the surgery, flaps were photographed and graphically rendered. Then, they were analyzed with AutoCAD software. Three biopsies (proximal, medial and distal) of each flap were collected for histological analysis. RESULTS: Macroscopic analysis showed that animals of the study group had greater necrotic areas (p=0.003) in the dorsal skin flaps. Additionally, histological analysis of the distal third of these flaps showed a tendency to less granulated tissue formation in animals treated with sildenafil. CONCLUSION: Sildenafil subdermally was associated with lower viability of the random skin flap in rats.